(untitled) (KYAMC Journal, 2013)
Aim: To observe the responses of radiation with concurrent chemo-radiation and radiation alone at the primary tumour sites and metastatic neck nodes of patients with head and neck cancers weekly during treatment, after completion of treatment and at 6 weeks interval after treatment. Methods: Randomizes prospective study was carried out in the Department of Radiotherapy, Dhaka Medical College and Hospital, Dhaka during the period of July 2003 to June 2004. Patients with histologic and/or cytologic confirmation of the diagnosis of squamous cell carcinoma of head and neck without distance metastasis were included in this study. After proper evaluation Arm-A was treated by concurrent chemotherapy with Inj. Cisplatinum 75mg/m2 on Day-1, Day-21 and Day-42 and conventional radiotherapy with a total dose of 60 Gy in 30 fractions in 6 weeks. Arm-B was treated by conventional radiotherapy with the same dose as that of Arm-A. Every patient was evaluated by monitoring routinely to see the responses. All the resultant informations were kept preserved on a prescribed data sheet. These informations were than analyzed statistically and results were compiled accordingly. Result: Out of 28 patients in Arm-A, complete desirable response was observed in 19 cases and partial response in 9 cases, where as out of 30 patients in Arm-B it was 7 and 23 cases respectively. Conclusion: Concurrent chemo-radiation showed better response than radiation alone, though toxicities were little bit higher but it was acceptable and easily manageable. DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13315 KYAMC Journal Vol.1(2) January 2011, 54-58